Vesiculopustular drug reaction with eosinophilia and systemic symptoms induced by levetiracetam - Thomas Norman; Jana Guenther; Kevin Wu; Brittney DeClerck; Scott Worswick (Wiley, 2024)
Abstract Drug reaction with eosinophilia and systemic symptoms (DRESS) is a severe cutaneous adverse reaction characterised by fever, lymphadenopathy, morbilliform rash, haematologic abnormalities, and multiorgan involvement. Herein, we describe a 32‐year‐old female presenting with a 9‐day history of facial oedema, cervical and inguinal lymphadenopathy, and a pruritic rash comprised of vesicles and pustules on her face, trunk, and extremities. Her only medications were valproate, which she had been taking for several years, and levetiracetam, which was initiated 41 days prior to rash onset. On the 16th day of her rash, she was diagnosed with DRESS induced by levetiracetam (Registry of Severe Cutaneous Adverse Reactions: 5). At this point, her absolute eosinophil count was 0.9 × 109 cells/L and aspartate and alanine transaminase levels were 357 and 339 U/L, respectively. Pustules with a morbilliform rash may occur in up to 30% of DRESS cases. In rarer instances, as in our patient, DRESS can present with isolated pustules and vesicles. Similarly, although rare, DRESS can be induced by levetiracetam.